Исследование тепловых процессов в линейном импульсно-индукционном электромеханическом преобразователе циклического действия - Болюх, Владимир Федорович; Щукин, Игорь Сергеевич (НТУ "ХПИ", 2017)
Разработана математическая модель линейного импульсно-индукционного электромеханического преобразователя (ЛИИЭП) циклического действия, система уравнений которой учитывает комплекс взаимосвязанных электромагнитных, электромеханических и тепловых процессов. Решения этих уравнений представлены в рекуррентном виде. Исследованы процессы ЛИИЭП, протекающие при прямом ходе рабочего цикла. Показано, что к концу рабочего цикла значительная часть энергии сохраняется в емкостном накопителе энергии, а также преобразуется в тепловую энергию якоря и индуктора. При значительном числе рабочих циклов происходит недопустимый нагрев активных элементов ЛИИЭП. Для решения этой проблемы используется интенсивное охлаждение обмотки индуктора, подвижного якоря или их обоих, а также увеличение периода следования импульсов. Установлено, что при работе ЛИИЭП в циклическом режиме экспериментальные зависимости температуры нагрева обмотки индуктора с точностью до 6 % совпадают с расчетными результатами. Разработана конструктивная схема ЛИИЭП циклического действия с интенсивным водяным охлаждением обмотки индуктора.

Investigation of the influence of the intensity of cooling of active elements and the period of succession of power pulses on the thermal processes of linear pulse-induction electromechanical converter (LPIEC) operating in a cyclic mode. Methodology. The electromechanical and energy processes of LPIEC, which arise during the direct course of the working cycle, are investigated. It is shown that by the end of the operating cycle, a significant part of the energy is stored in the capacitive energy storage device, and is also converted into thermal energy of the armature and inductor. With a significant number of operating cycles, an unacceptably high temperature rise of LPIEC active elements occurs. To solve this problem, intensive cooling of the winding of the inductor, the movable armature or both of them, as well as an increase in the pulse repetition period are used. It has been experimentally established that when the LPIEC is operating in a cyclic mode, the inductor winding with a steel frame blown with air is heated more slowly than the winding with an insulating frame. The experimental dependences with an accuracy of 6 % coincide with the calculated results. A constructive scheme of the LPIEC of cyclic action with intensive cooling of the stationary winding of the inductor has been developed. Results. A mathematical model of the LPIEC of cyclic action is developed, taking into account a complex of interrelated electromechanical and thermal processes. The solutions of its equations are represented in a recurrent form. The electromechanical and energy processes of LPIEC, which arise during the direct course of the working cycle, are investigated. It is shown that for a considerable number of operating cycles, unacceptably high temperature excesses of active elements of the LPIEC are observed. It is shown that intensive cooling of the winding of the inductor, the movable armature or both of them, and also the increase in the pulse repetition period ensure the temperature stabilization of the LPIEC. Measurements of the temperature on the surface of the winding of the inductor LPIEC during cyclic operation are carried out. A constructive scheme of the LPIEC of cyclic action with intensive cooling of the stationary winding of the inductor has been developed. Originality. A mathematical model of the LPIEC of cyclic action is developed, taking into account a complex of interrelated electromechanical and thermal processes. The solutions of its equations are represented in a recurrent form. It is shown that by the end of the working cycle a significant part of the energy is converted into thermal energy of the armature and inductor. It is determined that for a significant number of operating cycles, unacceptably high temperature excesses of active elements of the LPIEC are observed. It is shown that intense cooling of active elements, as well as an increase in the pulse repetition period, ensure the temperature stabilization of the LPIEC. A design scheme of the LPIEC with intensive cooling of the stationary winding of the inductor has been developed. Practical value. It is shown that by thermal cooling of at least one of the active elements and by increasing the pulse repetition period, the temperature stabilization of the LPIEC is ensured. A constructive scheme of the LPIEC of cyclic action with intensive cooling of the stationary winding of the inductor has been developed.
Investigation of thermal processes in a linear pulse-induction electromechanical converter of cyclic action
Keywords: электрические машины; тепловое состояние; математическая модель; энергетические процессы; электромеханические процессы; интенсивное охлаждение; экспериментальные исследования; конструктивная схема; linear pulse-induction electromechanical converter; cyclic action; thermal state; mathematical model; electromechanical processes; energy processes; intensive cooling; experimental studies; constructive scheme